1992
DOI: 10.1088/0953-2048/5/1s/001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically measured irreversibility temperatures in superconducting oxides and alloys

Abstract: Irreversibility temperatures T,(H) were magnetically measured for the aligned powders of superconducting oxides, La1.85Sr0.15Cu04, YBa2Cu307, Bi2Sr~CaCu208, and Bi2Sr2Ca2Cu3010, and for the metallic superconductors, Nb, Nbof the thermally activated flux creep and the lattice or the glass melting models for the irreversibility temperatures. Also, the measurement procedures for TI@) using a SQUID magnetometer are described in detail, since the measuring methods and the criteria which are used for T,(H) are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In the x-axis the reduced temperature is reported. The IL has been measured by observing the deformation of the response function in the SQUID magnetometer while changing from an irreversible to a reversible behavior, as suggested in [15]. By this procedure, the IL for J c → 0 and therefore the highest H g irr have been measured (the terminology is that of [16]).…”
Section: Resultsmentioning
confidence: 99%
“…In the x-axis the reduced temperature is reported. The IL has been measured by observing the deformation of the response function in the SQUID magnetometer while changing from an irreversible to a reversible behavior, as suggested in [15]. By this procedure, the IL for J c → 0 and therefore the highest H g irr have been measured (the terminology is that of [16]).…”
Section: Resultsmentioning
confidence: 99%
“…All results reported here were found to be scan-length independent for scans less than 4.0 cm. A similar IL seen in vibrating reed experiments on Nb foils [16]-with the sample held stationary in the solenoid-provides additional evidence that this result is not an artifact of the scanning process.Vanishing of the isothermal magnetic hysteresis has also been used to define an IL [15,17]. It has been reported that this method can give different results than the ZFC-FC method [15,20], but this was not seen in measurements on our sample.…”
mentioning
confidence: 87%
“…The resistivity ratio was 5.9. Fieldcooled (FC) and zero-field-cooled (ZFC) magnetization measurements were made in fields ranging from 10 to 3000 G. The procedure is well known and has been reported elsewhere [1,5,6,15,17]. The measurements were performed using a Quantum Design SQUID susceptometer with the sample aligned perpendicular to the magnetic field.…”
mentioning
confidence: 99%
See 2 more Smart Citations